DEICTIC ANALYSIS OF MINEFIELDS SONG LYRIC BY FAOUZIA FEAT. JOHN LEGEND - Illiyin, Zainata; Kusworo, Budik (Interling : International Journal of English Language Teaching, Literature and Linguistics, 2023)
This study aims to analyze the types and the references of deictic words which found in the "Minefields" song lyric. Not only deixis, the researcher also provides an analysis of language functions in this study so that readers/listeners can understand the meaning of this song precisely and deeply. This study is aimed not only at people who love songs, but also at students who have difficulty determining the references and meanings of literal translations, and can be very useful in improving their English proficiency. This study used a qualitative descriptive research method and analyzed the deictic words in the "Minefields" song lyric. The researcher collects data by searching the lyric script on internet then recorded the deictic words found in "Minefields" song lyric. Therefore, the researcher analyze song lyric based on the type and function of deixis, determine the meaning references and analyze the deictic words using the study of language functions. The data source was the "Minefields" song lyric script. In addition, This song tells the story of two people who have had an affair in the past. This song contains many deictic words and elements of language such as poetic, conative and so on. The researcher analyzed the data by using the theory of Stephen C. Levinson who divided deixis into five types, namely 1) personal deixis; 2) spatial deixis; 3) temporal deixis; 4) discourse deixis and 5) social deixis. Moreover, the researcher classified the deictic words were found into each types of deixis based on Levinson's theory. In addition, the researcher determine the reference of deictic words contained in the Minefields song lyric then analyze them using study of language functions. There are fourty collected data that were found in this song lyric by the researcher of which twenty three data belong to personal deixis, two spatial deictic words, four belong to temporal deixis and eleven of discourse deictic words. The researcher suggested other researchers to discover more about deixis uses different data sources not only in the lyrics but can also be used in radio, advertising, fairy tales and others. In addition, the researcher hopes that the next researchers can give more understanding not only about deixis, but also the reference meaning and language function in order to improve mastery and sharpen language instincts.